1965
DOI: 10.1017/s0305004100004163
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of two superposed fluids

Abstract: The dispersion equation describing the character of the equilibrium of two viscous incompressible superposed fluids under the action of gravity is considered in detail. Approximations for extreme wave-numbers are obtained and exact numerical results for particular cases are given. The existence of certain secondary modes is also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1967
1967
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…If one may judge from recent discussion of oscillations of two fluids separated by a plane interface, determining all of the significant features of droplet oscillation is scarcely likely to be a trivial matter. The work of Willson (1965) has shown, for example, that, contrary to the belief previously held by some workers, there are important aspects of wave propagation on and instability of plane interfaces which are not revealed by study of the special case of two fluids having equal kinematic viscosities. In particular, Willson established that if the two viscosities are equal but one fluid is of much greater density, there is a range of wavelengths in which only one mode of aperiodic decay exists although two modes are found when the fluids have equal kinematic viscosities.…”
Section: Behaviour When the Interface Is Freementioning
confidence: 65%
“…If one may judge from recent discussion of oscillations of two fluids separated by a plane interface, determining all of the significant features of droplet oscillation is scarcely likely to be a trivial matter. The work of Willson (1965) has shown, for example, that, contrary to the belief previously held by some workers, there are important aspects of wave propagation on and instability of plane interfaces which are not revealed by study of the special case of two fluids having equal kinematic viscosities. In particular, Willson established that if the two viscosities are equal but one fluid is of much greater density, there is a range of wavelengths in which only one mode of aperiodic decay exists although two modes are found when the fluids have equal kinematic viscosities.…”
Section: Behaviour When the Interface Is Freementioning
confidence: 65%
“…Only the derivation of Eq. (3) was in question because comparisons have shown that the formula itself is an excellent approximation to the exact results [22,23]. In Ref.…”
Section: Dispersion Relationsmentioning
confidence: 99%
“…We assume a small perturbation in the last system of eqs. (9)- (11) and consider the fluid to be arranged in horizontal strata, i.e., the density is a function of the vertical coordinate z only, and acted by gravity force g(0, 0, −g) and a homogeneous horizontal magnetic field H(H 0 , 0, 0). We put V = (u, v, w), H = (H x , H y , H z ); δρ and δp denote, respectively, the perturbations in density ρ and pressure p. Then the relevant linearized perturbations equations are…”
Section: Perturbation Equationsmentioning
confidence: 99%
“…here µ 1 , µ 2 are the viscosities of the lighter and heavier fluids, respectively, and T s is the surface tension at the interface. In the absence of surface tension equation (3), was proposed by Hide [8,9] and it was studied by Reid [10], Willson [11], and Plesset and Whipple [12]. Mikaelian [13] studied the effect of viscosity on RTI for two finite-thickness fluids in the presence of surface tension.…”
Section: Introductionmentioning
confidence: 99%